APLIKASI PENCARIAN RESEP MASAKAN KHAS BENGKULU MENGGUNAKAN ALGORITMA BINARY SEARCH BERBASIS ANDROID - Wijaya, Ardi; Maulana, M Fiqri; Danil, Muhammad (UNIVED Press, 2021)
Cooking is an activity that can be done by anyone. By cooking, someone can serve a variety of dishes on the dining table. Ingredients, spices and how to process food ingredients in making a dish can be seen in the recipe. Cooking Recipes are a guide for someone in processing food ingredients into dishes that can be served. The use of Android-based devices has increased very rapidly from year to year. One example is an application in the culinary field. Android device users can get a typical Bengkulu recipe application. Searching is a job that we often do in everyday life. One method that is efficient is the binary search method. Binary search can be done on a sequence of numbers that have been sorted, either ascending or descending. Based on the summary above, the author is interested in applying the binary search method to the Android-based search application for Typical Bengkulu Cooking Recipes, which aims to help and make things easier for users who need typical Bengkulu cooking recipes. Based on system testing with User Statisfaction Testing, it shows a value of 4.14 for the display variable, 4.2 for the user convenience variable value and 4.13 for the system performance variable value with these values ​​it can be concluded that the overall result is